Role of Spinal Diffusion Tensor Imaging in Predicting Post-operative Outcome in Cervical Degenerative Pathologies. Issue 1 (April 2016) - Ahmad, Faiz; Rindler, Rima; Eshraghi, Sheila; Chokshi, Falgun; Mossa-Basha, Mahmud; Buster, Bryan; Chu, Jason; Pradilla, Gustavo
Introduction: Predicting post-operative recovery after surgery for cervical spondylotic myelopathy (CSM) is challenging. The authors performed a systematic review of the literature evaluating the diagnostic ability of DTI in CSM, and its ability to predict post-operative outcome. Material and Methods: A systematic PubMED search adherent to PRISMA guidelines included relevant clinical studies reporting use of DTI in adult humans undergoing operative management for CSM from 1980 onwards. Available data on pre-operative clinical status and imaging and post-operative clinical outcomes were abstracted. Results: Six of 562 studies were eligible for detailed review. There were 112 patients with CSM and 45 healthy controls. Seventy-three (59.8%) underwent operative management with mean follow-up time 90–730 days. Fractional anisotropy (FA) was significantly lower in patients compared with controls across multiple studies, and correlated with pre-operative assessment (modified Japanese Outcome Assessment). FA and fiber tractography ratio (FTR) correlated with post-operative clinical assessments, with FA independently predicted surgical need and good outcome post-operatively. Conclusion: DTI may be a valuable tool in identifying patients in need of surgical decompression and predicting post-operative outcome. Future prospective studies are required for choosing optimal DTI parameters, anatomic levels and acquisition techniques.